Rubber metal laminate and gasket
The rubber metal laminate with a rubber layer of specific modulus and thickness addresses the challenge of maintaining sealing properties under compressive stress, preventing rubber layer slippage and ensuring excellent sealing performance.
Patent Information
- Application Number
- JP2022508258
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-17
- Filing Date
- 2021-03-10
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-03-10
AI Technical Summary
Conventional rubber metal laminates face challenges in preventing rubber layer deformation and maintaining sealing properties under compressive stress, as increased rubber hardness compromises lubricity and sealing efficiency.
A rubber metal laminate with a rubber layer having a 100% modulus value of 6.0 MPa or more and a thickness of less than 80 μm, which enhances the elastic modulus and prevents deterioration in processability and sealability, thereby preventing rubber layer slippage under compressive stress.
The solution effectively prevents rubber layer slippage and maintains excellent sealing properties even under compressive stress, ensuring the rubber metal laminate's performance and longevity.
Smart Images

Figure 0007670686000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber metal laminate and a gasket, and more particularly to a rubber metal laminate and a gasket in which a rubber layer is provided on a metal member. [Background technology]
[0002] Conventionally, metal gaskets have been proposed that are sandwiched between two members, such as the cylinder head and cylinder block of an internal combustion engine, to provide a seal (see, for example, Patent Document 1). This metal gasket comprises a rubber-metal laminate that includes a metal substrate and rubber layers provided on both main surfaces of the metal substrate. In the metal gasket described in Patent Document 1, the rubber-metal laminate is clamped between the cylinder head and the cylinder block to provide a seal between the members to be sealed, that is, the cylinder head and the cylinder block. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2003-130224 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the metal gasket described in Patent Document 1, a rubber-metal laminate is clamped between metal members such as a cylinder head and a cylinder block, so a strong compressive stress is applied to the rubber-metal laminate during use. In such a rubber-metal laminate, the application of compressive stress during use may cause the rubber layer to deform, causing the rubber to protrude from the rubber-metal laminate, and the desired function may not be obtained.
[0005] In order to improve the protrusion of rubber due to deformation of the rubber layer, it is effective to compound fillers such as carbon black and silica into the rubber layer to increase the hardness of the rubber layer. However, when the hardness of the rubber layer increases, the sealing ability of the rubber layer to the sealed object member may decrease. In addition, in order to improve the protrusion of rubber, it has been considered to increase the amount of sulfur used as a crosslinking agent in the rubber layer composition to increase the crosslink density of the rubber layer, but even if the crosslink density of the rubber layer is increased, a significant improvement effect on the protrusion of rubber is not expected. Thus, in the conventional rubber metal laminate, there are cases where the protrusion of rubber cannot be sufficiently improved by only increasing the hardness, and the relationship between the physical properties of rubber and the protrusion has not been found.
[0006] The present invention has been made in consideration of the above-mentioned situation, and aims to provide a rubber metal laminate and gasket that can prevent the rubber layer from protruding when compressive stress is applied and has excellent sealing properties for components to be sealed. [Means for solving the problem]
[0007] The rubber metal laminate of the present invention comprises a metal member and a rubber layer provided on the metal member, wherein the rubber layer has a 100% modulus value in accordance with JIS K6251 of 6.0 MPa or more and a thickness of less than 80 μm.
[0008] According to the rubber metal laminate of the present invention, the 100% modulus value of the rubber layer is 6.0 MPa or more and the thickness is less than 80 μm, so the elastic modulus of the rubber layer is appropriately improved. As a result, the rubber metal laminate can increase the hardness of the rubber layer by the filler. increase In comparison with the above case, deterioration of processability and sealing property during kneading of the rubber composition of the rubber layer can be prevented, and the elastic modulus required for the rubber layer can be secured. As a result, even when a compressive stress is applied to the rubber metal laminate, it is possible to better prevent the rubber layer from protruding from the rubber metal laminate, and it is possible to realize a rubber metal laminate with excellent sealing properties for the member to be sealed.
[0009] In the above rubber metal laminate, the rubber layer preferably has a 100% modulus value of 6.0 MPa or more in accordance with JIS K6251. With this configuration, the rubber metal laminate can prevent deterioration of processability and sealing properties during kneading, and can fully ensure the elastic modulus required for the rubber layer. As a result, even when a compressive stress is applied to the rubber metal laminate, it is possible to better prevent the rubber layer from protruding from the rubber metal laminate, thereby further improving the sealing properties of the member to be sealed.
[0010] In the rubber metal laminate, it is preferable that the rubber layer has an elongation value of 100% or more in accordance with JIS K 6251. With this configuration, the rubber metal laminate has an elongation value of the rubber layer in an appropriate range, so that even when a compressive stress is applied to the rubber metal laminate, it is possible to better prevent the rubber layer from protruding from the rubber metal laminate, and the sealing performance of the member to be sealed is further improved.
[0011] In the rubber metal laminate, the rubber layer preferably has a thickness of 25 μm or more. With this configuration, the relationship between the 100% modulus value and thickness of the rubber layer in the rubber metal laminate is in an appropriate range, and the elastic modulus of the rubber layer is further improved. As a result, even when a compressive stress is applied to the rubber metal laminate, it is possible to more effectively prevent the rubber layer from protruding from the rubber metal laminate, and the sealing performance of the member to be sealed is further improved.
[0012] In the rubber metal laminate, the rubber layer preferably contains 28% by mass or more of carbon black based on the total mass of the rubber layer. With this configuration, the rubber metal laminate can ensure the elastic modulus required for the rubber layer while preventing deterioration of sealing properties. As a result, even when compressive stress is applied to the rubber metal laminate, it is possible to better prevent the rubber layer from protruding from the rubber metal laminate, and the sealing properties of the sealed object are further improved.
[0013] In the rubber metal laminate, the metal plate and the rubber layer are preferably bonded together via at least one adhesive selected from the group consisting of phenolic resins and epoxy resins. This configuration improves the adhesion between the metal plate and the rubber layer, making it possible to better prevent the rubber layer from protruding from the rubber metal laminate and improving the sealing of the member to be sealed.
[0014] In the rubber metal laminate, it is preferable that the rubber layer contains nitrile rubber. With this configuration, the nitrile rubber contained in the rubber layer has appropriate elasticity, so that even when a compressive stress is applied to the rubber metal laminate, it is possible to prevent the rubber layer from protruding from the rubber metal laminate, and the sealing performance of the sealed object is further improved.
[0015] The gasket according to the present invention is characterized by comprising the above-mentioned rubber metal laminate.
[0016] According to the gasket of the present invention, the 100% modulus value of the rubber layer is 6.0 MPa or more and the thickness is less than 80 μm, so that the elastic modulus of the rubber layer is appropriately improved. As a result, compared to a case where the hardness of the rubber layer of the rubber metal laminate is increased by a filler, the gasket can prevent deterioration of the processability and sealing property during kneading of the rubber composition of the rubber layer and ensure the necessary elastic modulus of the rubber layer. As a result, even when a compressive stress is applied to the gasket, it is possible to better prevent the rubber layer from protruding from the rubber metal laminate, so that a gasket with excellent sealing properties for the member to be sealed can be realized. Effect of the Invention
[0017] According to the present invention, it is possible to prevent the rubber layer from protruding when compressive stress is applied, and it is possible to realize a rubber metal laminate and a gasket that have excellent sealing properties for members to be sealed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described in detail. The rubber metal laminate according to the embodiment of the present invention is suitable for use as a sealing member such as a gasket. The metal laminate according to the present embodiment includes a metal member and a rubber layer provided on at least one main surface of the metal member. The rubber layer has a 100% modulus value of 6.0 MPa or more and a thickness of less than 80 μm. Various components of the rubber metal laminate according to the present embodiment will be described in detail below.
[0019] (Metal parts) As the metal member, for example, a metal plate such as iron, stainless steel, aluminum, magnesium, galvanized steel, and copper is used. As the iron, for example, a cold rolled steel plate (SPCC: Steel Plate Cold Commercial), a high tensile steel plate, and a mild steel plate are used. As the stainless steel, for example, a stainless steel plate such as a ferritic, martensitic, or austenitic stainless steel plate can be used. Specific examples of the stainless steel include SUS304, SUS301, SUS301H, and SUS430. As the aluminum, an aluminum plate and an aluminum die-cast plate are used.
[0020] The metal member is preferably used after the surface has been degreased by an alkaline degreasing treatment, etc. Furthermore, the metal member is used after the metal surface has been roughened, if necessary, by shot blasting, Scotch Brite (registered trademark), hairline finishing, dull finishing, etc.
[0021] The metal member is preferably subjected to a surface treatment (surface treatment) on the surface to be bonded to the adhesive. The surface treatment is not particularly limited, and any known surface treatment can be used. When using iron materials such as cold-rolled steel sheets and high-tensile steel sheets and stainless steel materials as the metal member, the surface treatment is preferably a chemical conversion treatment method using various chemical conversion treatment agents, or various plating methods such as electroplating with metals such as zinc and hot-dip plating. Examples of chemical conversion treatment agents for metal members include phosphoric acid-based treatment agents such as zinc phosphate treatment agents and iron phosphate treatment agents, and paint-type chromate treatment agents. As the chemical conversion treatment agent, a chromium-free chemical conversion treatment agent that does not substantially contain chromium is preferable from the viewpoint of environmental protection.
[0022] The surface treatment of metal members with a chemical conversion treatment agent is carried out by contacting the chemical conversion treatment agent with the metal member by a known liquid contact method such as spraying, immersion, brushing, roll coating, etc. In the case of a reactive chemical conversion treatment agent, it is necessary to ensure the time and temperature required for the reaction.
[0023] The thickness of the metal member is appropriately set depending on the application of the rubber metal laminate. When the rubber metal laminate is used as a sealing material such as a gasket, the thickness of the metal member is, for example, preferably 100 μm or more and 2000 μm or less, more preferably 150 μm or more and 1000 μm or less, and even more preferably 200 μm or more and 500 μm or less.
[0024] In addition to or instead of the surface treatment, the rubber metal laminate preferably has a primer layer formed on the metal member. By carrying out the surface treatment or providing the primer layer, the adhesion between the rubber layer and the metal member in the rubber metal laminate is improved, and the heat resistance and water resistance of the rubber metal laminate can be significantly improved. Furthermore, by carrying out the surface treatment or forming the primer layer, the rubber metal laminate can be suitably used as a gasket, which is a laminated composite metal in which the rubber metal laminate is laminated with another metal plate or the like.
[0025] The primer layer can be provided by inorganic compounds such as silicon compounds, compounds of metals such as titanium, zirconium, vanadium, aluminum, molybdenum, tungsten, manganese, zinc, and cerium, and oxides thereof, and organic compounds such as silicone resins, phenolic resins, epoxy resins, and polyurethanes. The primer layer can be provided by using a primer solution that is generally available on the market, or by using a primer solution prepared by various known techniques.
[0026] The primer layer is provided by a primer solution in which raw materials containing the above-mentioned various inorganic compounds or organic compounds are dissolved or dispersed in an organic solvent or an aqueous solvent. Examples of organic solvents that can be used include alcohols such as methanol, ethanol, and isopropyl alcohol, and ketones such as acetone and methyl ethyl ketone. The primer solution may be prepared as an aqueous solution using an aqueous solvent as long as the liquid stability is maintained.
[0027] The obtained primer solution is applied onto a metal plate by spraying, dipping, brushing, roll coating, etc. Then, the primer layer is provided by drying the primer solution applied onto the metal plate at room temperature or with hot air, or by baking treatment.
[0028] (glue) The adhesive bonds the rubber layer and the metal member. As the adhesive, a commercially available adhesive such as a phenolic resin, an epoxy resin, a polyurethane resin, or a silane is used. These adhesives can be appropriately selected depending on the application of the rubber-metal laminate.
[0029] In the rubber metal laminate, the metal plate and the rubber layer are preferably bonded via at least one resin selected from the group consisting of phenolic resin and epoxy resin. This improves the adhesion between the metal plate and the rubber layer in the rubber metal laminate, making it possible to better prevent the rubber layer from protruding from the rubber metal laminate when compressive stress is applied, and further improving the sealing of the member to be sealed.
[0030] As the phenolic resin, for example, a novolac type phenolic resin and a resol type phenolic resin are used. The novolac type phenolic resin and the resol type phenolic resin may be used alone or in combination of two or more. In addition, as the adhesive, an adhesive containing two types of phenolic resins, a novolac type phenolic resin and a resol type phenolic resin, and an unvulcanized nitrile rubber may be used.
[0031] As the novolac type phenolic resin, one obtained by condensation reaction of phenols and formaldehyde in the presence of an acid catalyst is used. As the phenols, for example, phenol, p-cresol, m-cresol, p-tert-butylphenol, p-phenylphenol, bisphenol A, and the like, which have two or three substitutable hydrogen atoms at at least one of the o-position and p-position to the phenolic hydroxyl group, are used. These phenolic resins may be used alone or in combination of two or more. As the acid catalyst, for example, oxalic acid, hydrochloric acid, maleic acid, and the like are used. Among these, as the novolac type phenolic resin, one having a melting point of 80°C to 150°C is preferred from the viewpoint of improving the adhesion between the metal plate and the rubber layer, and the novolac type phenolic resin having a melting point of 120°C obtained by using m-cresol and formaldehyde is preferred. ℃ The above is more preferable.
[0032] The resol type phenolic resin is a resin obtained by condensing a phenol with formaldehyde in the presence of a base catalyst. The phenol may be, for example, phenol, p-cresol, m-cresol, p-tert-butylphenol, p-phenylphenol, bisphenol A, or the like, which has two or three substitutable hydrogen atoms at at least one of the o-position and p-position relative to the phenolic hydroxyl group. These phenolic resins may be used alone or in combination of two or more. The base catalyst may be, for example, ammonia, an alkali metal hydroxide such as sodium hydroxide, magnesium hydroxide, sodium carbonate, or the like.
[0033] Examples of epoxy resins include bisphenol A type, cresol novolac type, biphenyl type, and brominated epoxy resins. These epoxy resins may be used alone or in combination of two or more. Among these epoxy resins, bisphenol A type epoxy resins and cresol novolac type epoxy resins are preferred from the viewpoint of easy availability of commercial products and excellent heat resistance. As the bisphenol A type epoxy resin, for example, commercially available products such as "EPICLON 860", "EPICLON 1055", "EPICLON 2050", "EPICLON 3050", "EPICLON 4050", "EPICLON 7050", and "EPICLON HM-091" manufactured by DIC Corporation may be used. In addition, examples of commercially available cresol novolac epoxy resins that may be used include products under the trade names "EPICLON N-660," "EPICLON N-670," "EPICLON N-680," and "EPICLON N-690" manufactured by DIC Corporation.
[0034] The above-mentioned various adhesives are used as a solution dissolved in an organic solvent. Examples of the organic solvent include ketones such as methyl ethyl ketone and methyl isobutyl ketone, and aromatic hydrocarbons such as toluene and xylene. These organic solvents may be used alone or in combination of two or more.
[0035] The adhesive is preferably blended in a ratio of 10 to 1000 parts by mass of resol type phenolic resin per 100 parts by mass of novolac type phenolic resin, more preferably 60 to 400 parts by mass. By using 1000 parts by mass or less of resol type phenolic resin per 100 parts by mass of novolac type phenolic resin, it is possible to prevent a decrease in adhesion of the rubber layer, and by using 10 parts by mass or more, it is possible to prevent a decrease in adhesion to the surface of the metal member.
[0036] From the viewpoint of improving the adhesion between the metal member and the rubber layer, the adhesive is preferably provided on the metal plate on which the primer layer is formed. The adhesive layer may be provided as a single layer or as a multilayer. The adhesive layer may be provided as a multi-stage adhesive layer by forming a phenol-based adhesive layer containing an organometallic compound on the primer layer provided on the metal member, and then providing a phenol-based adhesive layer on the adhesive layer. By providing such an adhesive layer with a multi-stage structure, it is possible to further strengthen the adhesion between the primer layer and the rubber layer.
[0037] The adhesive is prepared as an adhesive solution with a solid content concentration of 1% by mass to 10% by mass using a ketone-based organic solvent such as acetone, methyl ethyl ketone, or methyl isobutyl ketone, or a mixture of these solvents. The adhesive solution is applied to a metal member, and then dried and baked for 1 to 30 minutes at a temperature of 100°C to 250°C to form an adhesive layer. The coating amount of the adhesive is 50 mg / m2 or more after drying and baking after application. 2 More than 2000mg / m 2 The thickness is preferably within the following range: The adhesive is preferably applied so that the thickness of the adhesive layer after drying is 0.5 μm or more and 5 μm or less.
[0038] (Rubber layer) In the rubber metal laminate according to the present embodiment, the rubber layer has a 100% modulus value of 6.0 MPa or more in accordance with JIS K6251. As a result, even when a high compressive stress is applied to the rubber metal laminate, the rubber layer has a moderate elastic modulus, and protrusion of the rubber layer from the rubber metal laminate can be suppressed, improving the sealing performance of the sealed member. In addition, the rubber metal laminate has a moderate elastic modulus without increasing the hardness of the rubber layer, preventing deterioration of processability and sealing performance during kneading, while maintaining the flexibility of the rubber, and improving the sealing performance of the sealed member. From the viewpoint of further improving the above-mentioned effects, the 100% modulus value of the rubber layer is more preferably 8.0 MPa or more, even more preferably 10 MPa, and more preferably 30 MPa or less, more preferably 25 MPa or less, and even more preferably 20 MPa or less.
[0039] Furthermore, in the rubber metal laminate according to this embodiment, the elongation value of the rubber layer in accordance with JIS K6251 is preferably 100% or more. This brings the elongation value of the rubber layer into an appropriate range, so that even if a compressive stress acts on the rubber metal laminate, it is possible to better prevent the rubber layer from protruding from the rubber metal laminate, and the sealing performance of the sealed object is further improved. From the viewpoint of further improving the above-mentioned effects, the elongation value of the rubber layer is more preferably 140% or more, even more preferably 170% or more, and is preferably 300% or less, more preferably 275% or less, and even more preferably 250% or less.
[0040] Furthermore, in the rubber metal laminate of this embodiment, from the viewpoint of obtaining an appropriate elastic modulus without excessively increasing the hardness of the rubber layer, and improving the sealing property of the components to be sealed while preventing deterioration of processability and sealing property during kneading, the hardness of the rubber layer in accordance with JIS K6253 is preferably 65 or more and 100 or less, more preferably 70 or more and 95 or less, and even more preferably 80 or more and 90 or less.
[0041] Furthermore, in the rubber metal laminate of this embodiment, from the viewpoint of preventing overhang of the rubber layer when compressive stress is applied while improving the sealing property of the component to be sealed, the tensile strength measured in accordance with JIS K6251 is preferably 7.5 MPa or more and 30 MPa or less, more preferably 10 MPa or more and 27.5 MPa or less, and even more preferably 12 MPa or more and 25 MPa or less.
[0042] The rubber layer can be obtained by using various rubber materials within the scope of the effects of the present invention. Examples of rubber materials include nitrile rubber (NBR: Nitrile Butadiene Rubber) which is an acrylonitrile-butadiene copolymer, hydrogenated nitrile rubber (HNBR) which is obtained by hydrogenating the unsaturated bond portion of nitrile rubber, and various rubber materials such as fluororubber. Among these, from the viewpoint of preventing the rubber layer from protruding from the rubber metal laminate and improving the sealing property, nitrile rubber and hydrogenated nitrile rubber are preferred, and nitrile rubber is more preferred. In addition, when the rubber layer is used for applications such as various gaskets such as automobile cylinder head gaskets, it is preferable that the rubber layer contains at least one selected from the group consisting of fluororubber and nitrile rubber, and it is preferable that the rubber layer contains nitrile rubber. In addition, by crosslinking the rubber layer, better heat resistance and adhesion can be obtained.
[0043] The nitrile rubber preferably has a bound acrylonitrile content of 18% or more and 48% or less, more preferably 31% or more and 42% or less, and even more preferably a medium-high nitrile content of 31% or more and less than 36%, from the viewpoints of improving the adhesion between the rubber layer and the adhesive and improving the cold resistance. Also, the nitrile rubber preferably has a Mooney viscosity ML 1+4 The rubber having a hardness (100° C.) of 30 to 85 is preferable, and an acrylonitrile-butadiene copolymer rubber having a hardness (100° C.) of 40 to 70 is used. In addition, as the nitrile rubber, a commercially available product such as "Nipol (registered trademark) DN3350" (manufactured by Zeon Corporation) may be used.
[0044] In addition, it is preferable that the rubber layer contains a rubber composition containing carbon black, from the viewpoint of improving the hardness of the rubber layer and preventing the rubber layer from protruding from the rubber metal laminate when compressive stress is applied to the rubber metal laminate.
[0045] Examples of carbon black include hard carbons such as super abrasion resistant (SAF) carbon black, intermediate super abrasion resistant (ISAF) carbon black, high abrasion resistant (HAF) carbon black, and easy processing channel (EPC) carbon black, as well as soft carbons such as eXtra Conductive Furnace (XCF) carbon black, fast extruding furnace (FEF) carbon black, general purpose furnace (GPF) carbon black, high modulus furnace (HMF) carbon black, semi-reinforcing furnace (SRF) carbon black, fine thermal (FT) carbon black, and medium thermal (MT) carbon black. These carbon blacks may be used alone or in combination of two or more. Among these, As the carbon black, soft carbon is preferred, and among the soft carbons, medium-reinforcing carbon black and medium-grain pyrolytic carbon black are more preferred. As the carbon black, a commercially available medium-grain pyrolytic carbon black such as the trade name "THERMAX (registered trademark) N990 LSR" (manufactured by Cancarb) may be used, or a commercially available medium-reinforcing carbon black such as the trade name "HTC♯SS" (manufactured by Nippon Steel Carbon Co., Ltd.) and the trade name "ASAHI♯50HG" (manufactured by Asahi Carbon Co., Ltd.) may be used.
[0046] The amount of carbon black to be mixed is preferably 50 parts by mass or more and 300 parts by mass or less, more preferably 70 parts by mass or more and 250 parts by mass or less, and even more preferably 85 parts by mass or more and 200 parts by mass or less, per 100 parts by mass of the rubber component, from the viewpoint of preventing the rubber layer from protruding from the rubber metal laminate when compressive stress is applied and improving sealing properties.
[0047] The amount of carbon black to be mixed is preferably 28% by mass or more and 80% by mass or less, more preferably 30% by mass or more and 70% by mass or less, and even more preferably 40% by mass or more and 60% by mass or less, based on the total mass of the rubber composition, from the viewpoint of preventing the rubber layer from protruding from the rubber metal laminate when compressive stress is applied and improving sealing properties.
[0048] Furthermore, when the carbon black is MT carbon, from the viewpoint of preventing the rubber layer from protruding from the rubber metal laminate when compressive stress is applied and improving sealing properties, the amount of carbon black compounded is preferably 50 parts by mass or more and 250 parts by mass or less, more preferably 70 parts by mass or more and 200 parts by mass or less, and even more preferably 85 parts by mass or more and 175 parts by mass or less, per 100 parts by mass of the rubber component.
[0049] When the carbon black is MT carbon, the amount of carbon black is preferably 28% by mass or more and 80% by mass or less, more preferably 30% by mass or more and 70% by mass or less, and even more preferably 40% by mass or more and 60% by mass or less, based on the total mass of the rubber composition, from the viewpoint of preventing the rubber layer from protruding from the rubber metal laminate when compressive stress is applied and improving sealing properties.
[0050] Furthermore, when the carbon black is SRF carbon, from the viewpoint of preventing the rubber layer from protruding from the rubber metal laminate when compressive stress is applied and improving sealing properties, the amount of carbon black compounded is preferably 35 parts by mass or more and 200 parts by mass or less, more preferably 45 parts by mass or more and 150 parts by mass or less, and even more preferably 50 parts by mass or more and 125 parts by mass or less, per 100 parts by mass of the rubber component.
[0051] When the carbon black is SRF carbon, the amount of carbon black is, from the viewpoint of preventing protrusion of the rubber layer from the rubber metal laminate when compressive stress is applied and improving sealing properties, preferably from 25 mass % to 70 mass %, more preferably from 27.5 mass % to 60 mass %, and even more preferably from 30 mass % to 50 mass %, relative to the total mass of the rubber composition.
[0052] The rubber composition is provided by applying the rubber composition onto a metal member or a primer layer and then crosslinking the rubber composition. The rubber composition preferably contains a vulcanizing agent and a vulcanization accelerator. As the vulcanizing agent, for example, commercially available products such as Colloidal Sulfur A (manufactured by Tsurumi Chemical Industry Co., Ltd.) and trade name "Vulnoc (registered trademark) R" (4,4'-dithiodimorpholine: manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) may be used. The compounding amount of the vulcanizing agent is, for example, 0.1 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the rubber component.
[0053] As the vulcanization accelerator, various sulfur-containing vulcanization accelerators such as guanidine-based, aldehyde-amine-based, aldehyde-ammonia-based, thiazole-based, sulfenamide-based, thiourea-based, thiuram-based, dithiocarbamate-based, and xanthate-based are used. Among these, as the sulfur-containing vulcanization accelerator, tetramethylthiuram disulfide, tetrabenzylthiuram disulfide, and N-cyclohexyl-2-benzothiazylsulfenamide are preferred. In addition, as the vulcanization accelerator, commercially available products such as the product name "Noccela (registered trademark) TBZTD" (tetrabenzylthiuram disulfide: manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), the product name "Noccela (registered trademark) CZ-P" (N-cyclohexyl-2-benzothiazylsulfenamide: manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), and "Noccela (registered trademark) TT-P" (tetramethylthiuram disulfide: manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) may be used. The compounding amount of the vulcanization accelerator is, for example, 1 part by mass or more and 20 parts by mass or less per 100 parts by mass of the rubber component.
[0054] The rubber composition may contain fillers such as calcium carbonate and silica, if necessary. As the calcium carbonate, various calcium carbonates such as heavy calcium carbonate and synthetic calcium carbonate may be used. As the calcium carbonate, a commercially available product such as "Whiten SB-Red" (heavy calcium carbonate, manufactured by Bihoku Funka Kogyo Co., Ltd.) may be used. The amount of calcium carbonate to be mixed is preferably, for example, 10 parts by mass or more and 100 parts by mass or less per 100 parts by mass of the rubber component.
[0055] As the silica, various kinds of silica can be used within the scope of the effect of the present invention. As the silica, for example, dry process silica produced by the thermal decomposition method of halogenated silicic acid or organic silicon compound, the method of heating and reducing silica sand to vaporize silicon oxide (SiO) and oxidizing it with air, and wet process silica produced by the thermal decomposition method of sodium silicate can be used. As the silica, for example, a commercially available product such as "Nipsil E-74P" (manufactured by Tosoh Silica Corporation) may be used. The compounding amount of silica is preferably, for example, 5 parts by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the rubber component.
[0056] The rubber composition may contain, as necessary, auxiliary agents commonly used in the rubber industry, such as a plasticizer, an acid acceptor such as zinc oxide, stearic acid, an antioxidant, and wax. Examples of the plasticizer include commercially available products such as "ADEKA CIZER (registered trademark) RS107" (manufactured by ADEKA CORPORATION). The blending amount of the plasticizer is, for example, 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the rubber component.
[0057] As the acid acceptor, for example, a commercially available product such as zinc oxide (manufactured by Seido Chemical Industry Co., Ltd.) may be used. As the stearic acid, for example, a commercially available product such as the product name "DTST" (manufactured by Miyoshi Oil & Fat Co., Ltd.) may be used. Furthermore, as the anti-aging agent, for example, a commercially available product such as the product name "Nocrac (registered trademark) 810-NA" (2,2,4-trimethyl-1,2-dihydroquinoline polymer: manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) may be used. Furthermore, as the wax, for example, a commercially available product such as the product name "Suntite (registered trademark) R" (microcrystalline wax: manufactured by Seiko Chemical Industry Co., Ltd.) may be used.
[0058] In the rubber metal laminate according to this embodiment, the rubber layer has a thickness of less than 80 μm. This brings the relationship between the 100% modulus value and thickness of the rubber layer into an appropriate range, so that even when a compressive stress acts on the rubber metal laminate, it is possible to better prevent the rubber layer from protruding from the rubber metal laminate, and the sealing performance of the sealed object is further improved. From the viewpoint of further improving the above-mentioned effects, the thickness of the rubber layer is preferably 30 μm or more, more preferably 40 μm to 75 μm, and even more preferably 45 μm to 70 μm.
[0059] <Method of manufacturing rubber metal laminate> The rubber metal laminate according to the above embodiment is manufactured by using a rubber composition obtained by mixing a metal member such as a stainless steel plate with a rubber component and carbon black, and mixing a vulcanizing agent, a vulcanization accelerator, calcium carbonate, silica, a plasticizer, and various auxiliaries as necessary, in a kneading machine such as an intermix, kneader, or Banbury mixer, or an open roll. The rubber metal laminate is manufactured by applying the above rubber composition to a metal member, which has been surface-treated as necessary, via an adhesive layer, and then vulcanizing the rubber composition under conditions of 160°C to 250°C for 0.5 to 30 minutes, for example, to form a rubber layer. The rubber composition is preferably applied so that the thickness of the rubber layer after application is 50 μm to 200 μm. In addition, the rubber metal laminate may be coated with a coating agent such as a resin-based or graphite-based coating agent on the rubber layer from the viewpoint of preventing adhesion of the rubber.
[0060] The method for applying the rubber composition to the metal member is not particularly limited as long as the rubber composition can be applied to the metal member. Application method Examples of the method include a spray method, a dipping method, a roll coating method, and a dispenser method.
[0061] When the rubber composition is produced and applied to a metal member, an organic solvent may be added to the rubber composition to adjust the viscosity as necessary. The organic solvent is not particularly limited as long as it can adjust the viscosity of the rubber composition to a desired viscosity. Examples of the organic solvent include methyl ethyl ketone, toluene, and ethyl acetate. These organic solvents may be used alone or in combination of two or more.
[0062] As described above, according to the above embodiment, the 100% modulus value of the rubber layer is 6.0 MPa or more and the thickness is less than 80 μm, so that the elastic modulus of the rubber layer is appropriately improved. As a result, the rubber metal laminate can prevent deterioration of the processability and sealing property during kneading of the rubber composition of the rubber layer, and can ensure the elastic modulus required for the rubber layer, compared to the case where the hardness of the rubber layer is increased by a filler. As a result, even when a compressive stress is applied to the rubber metal laminate, it is possible to further prevent the rubber layer from protruding from the rubber metal laminate, so that a rubber metal laminate with excellent sealing properties for the sealed object can be realized. Furthermore, in the rubber metal laminate, protruding properties have been improved by simply increasing the hardness of the rubber, but by developing with a focus on the 100% modulus value, protruding properties can be ensured even at low hardness, and improved sealing properties can be expected. Furthermore, since the protruding properties of the rubber layer when compressive stress is applied can be predicted by the 100% modulus value without actually creating the rubber metal laminate, it leads to a reduction in the evaluation process.
[0063] Furthermore, according to the above embodiment, a gasket including a rubber metal laminate is obtained. As a result, the 100% modulus value of the rubber layer is 6.0 MPa or more and the thickness is less than 80 μm, so that the elastic modulus of the rubber layer is appropriately improved. As a result, compared to a case where the hardness of the rubber layer is increased by a filler, the gasket can prevent deterioration of the processability and sealing property during kneading of the rubber composition of the rubber layer and can ensure the elastic modulus required for the rubber layer. As a result, even when a compressive stress is applied to the gasket, it is possible to further prevent the rubber layer from protruding from the gasket, so that a gasket with excellent sealing properties for the member to be sealed can be realized. EXAMPLES
[0064] The present invention will be described in more detail below based on examples carried out to clarify the effects of the present invention. Note that the present invention is not limited to the following examples and comparative examples.
[0065] The present inventors have produced the rubber metal laminate according to the above embodiment, and have carried out a compression test to evaluate the produced rubber metal laminate. The results of the investigation carried out by the present inventors will be described below.
[0066] Example 1 <Rubber Thermoplastics (TP) Evaluation> Nitrile butadiene rubber (trade name "Nipol DN3350", manufactured by Zeon Corporation) 100 parts by mass, carbon black A (medium thermal (MT) carbon black, trade name "THERMAX N990 LSR", manufactured by Cancarb Corporation) 90 parts by mass, zinc oxide (manufactured by Seido Chemical Industry Co., Ltd.) 5 parts by mass, stearic acid (trade name "DTST", manufactured by Miyoshi Oil Co., Ltd.) 1 part by mass, antioxidant (2,2,4-trimethyl-1,2-dihydroquinoline polymer, trade name "Nocrac 810-NA", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) 2 parts by mass, microcrystalline wax (trade name "Suntite R", manufactured by Seiko Chemical Co., Ltd.) 2 parts by mass, vulcanizing agent A (colloidal sulfur A, manufactured by Tsurumi Chemical Industry Co., Ltd.) 1.5 parts by mass, vulcanizing agent B (4,4'-dithiodimorpholine, trade name "Vulnoc A rubber composition was obtained by kneading 1 part by mass of vulcanization accelerator A (tetrabenzyl thiuram disulfide: trade name "Noccela TBZTD", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 5 parts by mass of vulcanization accelerator A (N-cyclohexyl-2-benzothiazyl sulfenamide: trade name "Noccela CZ-P", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) with a kneader and an open roll. Next, the rubber composition was pressurized at 170 ° C for 8 minutes to be vulcanized, and a rubber sheet having a thickness of 2 mm was produced. The hardness of the obtained rubber sheet was measured in accordance with JIS K6253, and the 100% modulus value, tensile strength, and elongation were measured in accordance with JIS K6251.
[0067] <Preparation of samples for compression test evaluation> On a cold-rolled steel plate (SPCC: Steel Plate Cold Commercial) with a thickness of 250 μm that had been surface-treated with a zinc phosphate treatment agent, 100 parts by mass of phenolic resin (trade name "Sixon 715A" 97% by mass, trade name "Sixon 715N" 3% by mass, both manufactured by Rohm and Haas Co.) was diluted with an organic solvent of 440 parts by mass of methyl ethyl ketone and 110 parts by mass of methanol, and the adhesive was applied to a thickness of 3 μm and dried at room temperature. Next, the rubber composition of the compounding used in the thermoplastic evaluation was dissolved in an organic solvent to adjust the viscosity to about 1000 to 10000 mPa·s, and further applied to the cold-rolled steel plate coated with the phenolic resin so that the thickness of the rubber layer after curing was 65 μm, and then vulcanized in an oven at 200 ° C for 3 minutes to prepare a compression test evaluation sample of the rubber laminated metal plate. Here, an anti-adhesion layer may be applied as necessary. The prepared compression test evaluation sample was evaluated by the following evaluation method. The results are shown in Table 1 below.
[0068] <Compression test evaluation> Compression test of rubber-laminated metal sheet: A donut-shaped convex metal fitting was pressed against the rubber layer of the evaluation sample at 150 MPa for 5 minutes at 150°C, and the condition of the rubber layer was then evaluated based on the following criteria. 5 points: No exposed metal and almost no rubber flow. 4 points: No exposed metal and only a small amount of rubber flow. 3 points: There is some rubber flow, but the metal has not yet been exposed. 2 points: There is a lot of rubber flow but little exposed metal. 1 point: Large rubber flow and metal exposure.
[0069] Example 2 Except for changing the compounding amount of carbon black A to 151 parts by mass, a sample for evaluating the compression test of the rubber-laminated metal plate was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1 below.
[0070] Example 3 A compression test evaluation sample of the rubber laminated metal sheet was prepared and evaluated in the same manner as in Example 1, except that 65 parts by mass of carbon black B (SRF carbon black: product name "HTC♯SS", manufactured by Nippon Steel Carbon Co., Ltd.) was used instead of carbon black A. The results are shown in Table 1 below.
[0071] Example 4 A compression test evaluation sample of the rubber-laminated metal plate was prepared and evaluated in the same manner as in Example 3, except that the blending amount of carbon black B was 104 parts by mass. The results are shown in Table 1 below.
[0072] Example 5 Except for changing the thickness of the rubber layer to 50 μm, a sample for evaluating a compression test of the rubber-laminated metal plate was prepared and evaluated in the same manner as in Example 4. The results are shown in Table 1 below.
[0073] Example 6 A compression test evaluation sample of the rubber laminated metal plate was prepared and evaluated in the same manner as in Example 1, except that 56 parts by mass of carbon black C (Semi-Reinforcing Furnace (SRF) carbon black: product name "ASAHI♯50HG", manufactured by Asahi Carbon Co., Ltd.) was used instead of carbon black A. The results are shown in Table 1 below.
[0074] Example 7 A compression test evaluation sample of a rubber-laminated metal sheet was prepared and evaluated in the same manner as in Example 1, except that 90 parts by mass of carbon black C was used instead of carbon black A. The results are shown in Table 1 below.
[0075] Example 8 A compression test evaluation sample of the rubber laminated metal sheet was prepared and evaluated in the same manner as in Example 1, except that the blending amount of carbon black A was 181 parts by mass and 10 parts by mass of a plasticizer (product name "Adeka Cizer RS107", manufactured by ADEKA CORPORATION) was used. The results are shown in Table 1 below.
[0076] Example 9 A compression test evaluation sample of the rubber laminated metal plate was prepared and evaluated in the same manner as in Example 1, except that the amount of carbon black A was 40 parts by mass, 60 parts by mass of carbon black B was used, 60 parts by mass of calcium carbonate (trade name "Whiten SB-Red", manufactured by Bihoku Funka Kogyo Co., Ltd.) was used, 30 parts by mass of silica (trade name "Nipsil E-74P", manufactured by Tosoh Silica Corporation) was used, and no vulcanizing agent B was used. The results are shown in Table 1 below.
[0077] Comparative Example 1 Except for changing the compounding amount of carbon black A to 45 parts by mass, a sample for evaluating the compression test of the rubber-laminated metal plate was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1 below.
[0078] Comparative Example 2 A compression test evaluation sample of the rubber-laminated metal plate was prepared and evaluated in the same manner as in Example 3, except that the blending amount of carbon black B was 31 parts by mass. The results are shown in Table 1 below.
[0079] Comparative Example 3 A compression test evaluation sample of the rubber-laminated metal plate was prepared and evaluated in the same manner as in Example 6, except that the blending amount of carbon black C was 30 parts by mass. The results are shown in Table 1 below.
[0080] Comparative Example 4 A compression test evaluation sample of the rubber laminated metal plate was prepared and evaluated in the same manner as in Example 1, except that the amount of carbon black A was 65 parts by mass, 60 parts by mass of calcium carbonate (trade name "Whiten SB-Red", manufactured by Bihoku Funka Kogyo Co., Ltd.) was used, and 5 parts by mass of silica (trade name "Nipsil E-74P", manufactured by Tosoh Silica Corporation) was used. The results are shown in Table 1 below.
[0081] [Table 1]
[0082] Details of each component in Table 1 above are as follows. NBR: Nitrile rubber (medium-high nitrile (bound acrylonitrile content 31% to less than 36%): product name "Nipol DN3350", manufactured by Zeon Corporation) Carbon black A: Medium thermal (MT) carbon black (product name "THERMAX N990 LSR", manufactured by Cancarb) Carbon black B: Semi-reinforcing furnace (SRF) carbon black (product name "HTC♯SS", manufactured by Nippon Steel Carbon Co., Ltd.) Carbon black C: SRF carbon black (product name "ASAHI♯50HG", manufactured by Asahi Carbon Co., Ltd.) Calcium carbonate: Product name "Whiten SB-Red" (manufactured by Bihoku Powder Industry Co., Ltd.) Silica: Product name "Nipsil E-74P" (manufactured by Tosoh Silica Corporation) Plasticizer: Product name "Adeka Cizer RS107" (manufactured by ADEKA Corporation) Zinc oxide (manufactured by Seido Chemical Industry Co., Ltd.) Stearic acid: Trade name "DTST" (manufactured by Miyoshi Oil Co., Ltd.) Antioxidant: 2,2,4-trimethyl-1,2-dihydroquinoline polymer (product name "Nocrac 810-NA", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) Wax: Wax (product name "Suntite R", manufactured by Seiko Chemical Co., Ltd.) Vulcanizing agent A: Colloidal sulfur A (Tsurumi Chemical Industry Co., Ltd.) Vulcanizing agent B: 4,4'-dithiodimorpholine (product name "Valnoc R", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) Vulcanization accelerator A: Tetrabenzyl thiuram disulfide (product name "Noccela TBZTD", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) Vulcanization accelerator B: N-cyclohexyl-2-benzothiazylsulfenamide (product name "Noccela CZ-P", manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0083] As can be seen from Table 1, in the rubber metal laminate according to the above embodiment, since the 100% modulus value of the rubber layer is 6.0 MPa or more, the rubber flow in the compression test is relatively small, and all of the scores in the overhang evaluation were 4 points or more (Examples 1 to 9). In addition, regarding carbon black, regardless of whether medium-grain pyrolytic carbon black or medium reinforcing carbon black was used, the overhang evaluation scores were all 4 points or more (Examples 1 to 7). In addition, even when the thickness of the rubber layer was changed to 50 μm, the rubber flow in the compression test was hardly observed, and the overhang evaluation score was 5 points (Example 5). In addition, even when a plasticizer was blended, since the 100% modulus value of the rubber layer was 6.0 MPa or more, the rubber flow in the compression test was hardly observed, and the overhang evaluation score was 5 points (Example 8). Furthermore, even when calcium carbonate and silica were blended, when the 100% modulus value of the rubber layer was 6.0 MPa or more, the flow of the rubber in the compression test was relatively small, and the evaluation of the sticking property was scored as 5 points (Example 9).
[0084] In contrast, when the 100% modulus value of the rubber layer is less than 6.0 MPa, the flow of the rubber in the compression test is large, and the evaluation of the sticking out property is scored as 1 to 3 points (Comparative Examples 1 to 4).
[0085] From the above results, it can be seen that according to the above embodiment, by making the 100% modulus value of the rubber layer 6.0 MPa or more and making the thickness of the rubber layer less than 80 μm, it is possible to prevent the rubber layer from protruding even when compressive stress is applied to the rubber metal laminate, and the sealing properties of the rubber metal laminate are improved. [Industrial Applicability]
[0086] As described above, according to the above-mentioned embodiment, it is possible to prevent the rubber layer from protruding when compressive stress is applied, and it is possible to realize a rubber metal laminate and a gasket that have excellent sealing properties for members to be sealed, and they can be suitably used in various gaskets such as cylinder head gaskets, etc. Furthermore, according to the above-mentioned embodiment, they can be used in other applications such as compressors, water pumps, motors, batteries, power control units, inverter cases, etc.
[0087] Although one embodiment of the present invention has been described above, the embodiment of the present invention is not limited to the contents of this embodiment. The above-mentioned components include those that a person skilled in the art can easily imagine, those that are substantially the same, and those that are within the so-called equivalent range. Furthermore, the above-mentioned components can be appropriately combined. Furthermore, various omissions, substitutions, or modifications of the components can be made without departing from the gist of the above-mentioned embodiment.
Claims
1. A metal member; a rubber layer provided on the metal member, The rubber layer has a 100% modulus value in accordance with JIS K6251 of 6.0 MPa or more and a thickness of 50 μm or more and 65 μm or less, The rubber layer contains nitrile rubber and one type of carbon black, The carbon black is SRF carbon, A rubber metal laminate, characterized in that the blending amount of the carbon black is 56 parts by mass or more per 100 parts by mass of the rubber component.
2. 2. The rubber metal laminate according to claim 1, wherein the rubber layer has a 100% modulus value of 8.0 MPa or more in accordance with JIS K6251.
3. 3. The rubber metal laminate according to claim 1, wherein the rubber layer has an elongation value of 100% or more in accordance with JIS K6251.
4. 4. The rubber metal laminate according to claim 1, wherein the rubber layer contains 28 mass % or more of carbon black based on the total mass of the rubber layer.
5. 5. The rubber metal laminate according to claim 1, wherein the metal member and the rubber layer are bonded together via at least one adhesive selected from the group consisting of phenolic resins and epoxy resins.
6. A gasket comprising the rubber metal laminate according to any one of claims 1 to 5.
Citation Information
Patent Citations
Fluororubber composition
JP1996193153A
Rubber laminated metal plate
JP1999216799A
Rubber composition for molding oil seal member and oil seal member using the same
JP2002003648A
Metal gasket
JP2003130224A
Cylinder head gasket material for engine
JP2004011576A